Illicit drug intervention at grassroots: a community upliftment model - Ramson, Shakti (Acta criminologica, 2017)
The increasing percentage of youth reporting to addiction centres and clinics for treatment, positions illicit drug abuse as a major health and social issue in the Western Cape (The South African Community Epidemiology Network on Drug Use (SACENDU), 2015; Fakier & Louw, 2009). The Youth Research Forum (UNISA Bureau of Marketing, 2012) suggests that innovative and multi-faceted approaches to drug and alcohol prevention be introduced. This is underscored by Chetty (2015:60) who also proposes that school and community support programmes must foreground “normative principles of welfare, wellness, respect, ethics and caring for each other as fundamental steps for the social well-being of poor communities”. Given such calls, this article argues that there are innovative prevention initiatives that community members are attempting in addressing the problem. This article derives from a larger qualitative study of a Cape Flats community, which sought to understand the environmental and personal contexts of children that impel them towards gangsterism and illicit drug use. What emerged from the data was an innovative community upliftment model being implemented by a self-reformed gangster and drug user. This exploration is not an advocacy of that initiative, but an attempt to explain the workings of this model. The article reviews the research concerning community intervention in illicit drug use, provides a description about the methodology used in this study and undertakes a thematic analysis of the voices of the participants, namely: 1) the family and home contexts of children in the community, and 2) a community upliftment project. It is suggested working at the level of children and youth with a prevention model that invests personal care and a warm, loving family environment for those children that are denied this, may be a preventative strategy to help children make positive choices to reduce illicit drug use and other risky behaviour for future generations.